М. SCHUMPETER’S INNOVATION PARADIGM AND PRINCIPLES OF ECONOMIC SYSTEM REORGANIZATION - M. Kravchenko; E. Shergelashvili (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
The paper is devoted to the principles of the reorganization of the economic system of Ukraine. The principles of the economic system reorganization presented in the paper as a consequence Schumpeter’s theory of economic development. The main idea of the article is that institutions of modern society should systematically promote the establishment, operation and development of a new appropriation form that follows from both the role of innovation as a factor in Schumpeter’s theory of economic development and the role of social factors.